2020
DOI: 10.1186/s13006-020-00303-x
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, motivation and planning of breastfeeding: a cross-sectional study among Jordanian women

Abstract: Background: In Jordan, the rate of exclusive breastfeeding is declining. The trend variation in breastfeeding practice is determined by different factors including antenatal women's attitude and planning which are affected by their awareness and the support they receive. This study aims to assess knowledge, attitude, support, and planning of breastfeeding among Jordanian women. Methods: A face-to-face cross-sectional semi-structured questionnaire survey was conducted among healthy women in the antenatal clinic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 27 publications
2
23
2
2
Order By: Relevance
“…As infant feeding decisions appear to be made prenatally [ 18 ], pregnant women represent a key population of interest for characterizing the culturally prevalent norms, knowledge, and attitude towards BF, and for identifying misconceptions and negative perceptions that may lead to inadequate BF practices [ 19 21 ]. Studies have shown that the determinants of BF initiation, duration, and exclusivity are multifactorial and operate at multiple levels [ 10 , 11 , 22 29 ]. They include demographic and socioeconomic factors such as maternal age, education, parity, monthly income, and mother’s working status [ 23 ]; community support and structural factors; sociocultural beliefs and misconceptions prevalent in the community and among healthcare practitioners [24─26], as well as personal factors such as knowledge about the benefits of BF [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As infant feeding decisions appear to be made prenatally [ 18 ], pregnant women represent a key population of interest for characterizing the culturally prevalent norms, knowledge, and attitude towards BF, and for identifying misconceptions and negative perceptions that may lead to inadequate BF practices [ 19 21 ]. Studies have shown that the determinants of BF initiation, duration, and exclusivity are multifactorial and operate at multiple levels [ 10 , 11 , 22 29 ]. They include demographic and socioeconomic factors such as maternal age, education, parity, monthly income, and mother’s working status [ 23 ]; community support and structural factors; sociocultural beliefs and misconceptions prevalent in the community and among healthcare practitioners [24─26], as well as personal factors such as knowledge about the benefits of BF [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The intention to breastfeed is in turn influenced by maternal knowledge and attitude towards BF as well as the mother’s prior exposure to BF [ 31 , 32 ]. Several cross-sectional studies conducted among pregnant women have established a link between BF exposure, knowledge, and attitude, with the intention to BF prenatally [ 20 , 23 , 29 , 33 ]. However, few studies have investigated, longitudinally, the association between these maternal prenatal attributes and actual BF practices postnatally [ 22 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although research documenting breastfeeding attitudes has previously been published in various settings in Malaysia [10][11][12], to the best of our knowledge, this is the first study in Malaysia to employ a validated IIFAS scale to measure the breastfeeding attitudes of mothers with premature infants in NICUs during the COVID-19 pandemic. It was found that the average score for breastfeeding attitude (66.30 ± 6.92) is above the cut-off point (≥65), indicating that these mothers had a positive attitude towards breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…Breastfeeding attitude, which encompasses belief and knowledge, is defined as women's predisposition to express feelings, thoughts, and behaviours associated with a psychological mindset in developing their breastfeeding behaviour [10]. A previous study evidenced that mothers with a positive attitude are highly knowledgeable about breastfeeding [11] and intend to undertake actual and exclusive breastfeeding [12].…”
Section: Introductionmentioning
confidence: 99%